Comparison of two codon optimization strategies enhancing recombinant Sus scrofa lysozyme production in Pichia pastoris - Zhu, D; Cai, G; Wu, D; Lu, J (Cellular and Molecular Biology, 2015)
Lysozyme has played an important role in animal feed additive industry, food additive industry and biological engineering. For improving expression efficiency of recombinant lysozyme from Sus scrofa, two genes respectively designed by the most used codon optimization strategies, "one amino acid one codon” and "codon randomization”, were synthesized and expressed in Pichia pastoris X-33. At shaking flask level, Sus scrofa lysozyme (SSL) under two conditions had a highest activity of 153.33±10.41 and 538.33±15.18 U/mL after a 5 days induction of 1% methanol, with secreted protein concentration 80.03±1.94 and 239.60±4.16 mg/L, respectively. Compared with the original SSL gene, the expression of optimized SSL gene by the second strategy showed a 2.6 fold higher level, while the first method had no obvious improvement in production. In total secreted protein, the proportions of recombinant SSL encoded by the original gene, first method optimized gene and the second-strategy optimized one were 75.06±0.25%, 74.56±0.14% and 79.00±0.14%, respectively, with the same molecular weight about 18 kDa, optimum acidity pH 6.0 and optimum temperature 35degC.